2011
DOI: 10.1021/cm102231b
|View full text |Cite
|
Sign up to set email alerts
|

Application of Molecular Simulation Techniques to the Study of Factors Affecting the Thin-Film Morphology of Small-Molecule Organic Semiconductors

Abstract: We provide a short review of the status of using atomic- or molecular-scale simulations to look at the phenomena associated with growing thin films of small organic semiconductor materials, such as surface diffusion, thin film growth, Ehrlich−Schwoebel step-edge barrier, etc. We offer a summary of the advantages and limitations of existing computational tools (Molecular Dynamics, kinetic Monte Carlo, ab initio methods, etc.) and hint at method development that may help to deepen our understanding of “functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 211 publications
0
46
0
Order By: Relevance
“…Additionally the majority of the knowledge for inorganic semiconductors [8,9] is not immediately transferable to organic semiconductors, because of the anisotropy of organic semiconductor molecules and the vast number of different molecules with different anisotropic physiochemical properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally the majority of the knowledge for inorganic semiconductors [8,9] is not immediately transferable to organic semiconductors, because of the anisotropy of organic semiconductor molecules and the vast number of different molecules with different anisotropic physiochemical properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…
1985wileyonlinelibrary.com in favorable cases by atomistic molecular dynamics (MD) simulations. [ 9,[13][14][15][16] Further development in improving the performance of OSC requires a deeper knowledge and ability to control the molecular organization at the interface between the materials playing the role of electron donor and acceptor. Important factors are the choice of donors and acceptors chemical nature, their morphology and the type of heterojunction, which currently consists of either a planar interface between two thin layers of donor and acceptor (bilayer cell, [ 17 ] possibly replicated) tandem cells, [ 18,19 ] or an interpenetrated bicontinuous arrangement where the D, A materials are microsegregated inside a single photoactive layer (bulk heterojunction or BHJ).
…”
mentioning
confidence: 99%
“…However, this issue has not yet been fully elucidated. On the other hand, many computational calculations have demonstrated that molecular dynamics (MD) simulation is a well-known tool to investigate molecular behavior and it can provide valuable microscopic information to understand the mechanism of the growth of thin film [20]. Fichthorn and co-workers used MD simulations to study the melting of pentane, whose results of the temperature-dependent structures and the melting temperatures agree well with 3 experiment [21].…”
Section: Introductionmentioning
confidence: 91%